RESEARCH WORK AS A WAY OF FORMATION OF THE STUDENT'S CREATIVE PERSONALITY - С. Балашова; Н. Головко (Київський національний університет імені Тараса Шевченка, 2016)
The article is devoted to one of the most important elements of the educational process in higher education – students research work. In the article highlited the approaches to definition of "research work" and "educational-research work" in higher education. The article revealed the characteristic features of the research work, its structure, differences singled research students from teaching and research. In the article the stages of organization of research work, its forms and methods, and principles of its organization.

У статті розглянуті підходи до визначення поняття науково-дослідницька робота та розглянуто принципи, етапи, форми та методи дослідницької роботи у вищому навчальному закладі.
НАУКОВО-ДОСЛІДНИЦЬКА РОБОТА ЯК ЗАСІБ ТВОРЧОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ
Keywords: дослідницька діяльність студентів; науково-дослідницька робота; навчально-дослідницька робота; творча діяльність; творчі здібності; research activity of students; research work; teaching and research work; creative work; creative skills